A New assembly precision prediction method of aeroengine high-pressure rotor system considering manufacturing error and deformation of parts. (October 2021) - Mu, Xiaokai; Wang, Yunlong; Yuan, Bo; Sun, Wei; Liu, Chong; Sun, Qingchao
Highlights: The accurate prediction of rotor system assembly precision is the premise of improving aeroengine assembly quality. A new assembly precision prediction model considering the manufacturing error and deformation of parts is constructed. The new assembly precision prediction model is closer to the actual working conditions than the existing model. The assembly precision prediction model provides a model basis for improving product quality. Abstract: The accurate prediction of high-pressure rotor system assembly precision before assembly is the premise of improving aeroengine assembly quality and performance. The existing assembly precision prediction models (APPM) only consider the manufacturing error factors of parts, but rarely involve the deformation of parts under load, so there is a certain gap between the prediction results and the actual situation. This article studies the construction method of APPM considering the manufacturing error and deformation factors of parts. Firstly, the fitting algorithm is used to obtain the fitting deformation surface(FDS) of each mating surface under load, which provides the basis for constructing assembly error model considering manufacturing error and deformation of parts; secondly, according to the relative position relationship between the FDS and the datum plane, the error model of each mating surface of the assembly is effectively constructed by the small displacement torsor theory; thirdly, according to the different errors of each fitting end face, a prediction model of assembly precision for two rough surfaces is constructed by homogeneous coordinate transformation method; finally, a high-pressure compressor rotor system is used as an example to verify the effectiveness of the precision prediction model. The results show that the prediction results based on the proposed model are closer to the actual conditions. This paper provides an effective prediction model for high-pressure rotor system assembly precision, and has important application value for improving the assembly quality and performance of aeroengine.